Acute Primary Angle Closure: Case Report - Reinne Natali Christine (Indonesian Journal of Global Health Research, 2025)
Acute primary angle-closure is an ocular emergency caused by the rapid increase in intraocular pressure due to outflow obstruction of aqueous humor. The major predisposing factor is the structural anatomy of the anterior chamber, leading to a shallower angle between the iris and the cornea. The medical treatment for acute angle-closure glaucoma aims to decrease the intraocular pressure by blocking the production of aqueous humor, increasing the outflow of aqueous humor, and reducing the volume of the aqueous humor. Iridotomy laser should be chosen to open the angle blockage, while trabeculectomy is occasionally performed on eyes that do not respond to medical therapy. Aims to comprehensively describe the management and clinical course of a patient with primary acute angle closure (PAAC). This report also aims to improve clinicians' understanding of the importance of early diagnosis, appropriate treatment, and long-term follow-up in preventing complications that can lead to permanent vision loss. This study is a descriptive study with a case report design. Data were obtained retrospectively from the medical records of patients diagnosed with acute primary angle closure at Christian University Hospital, Jakarta. Information collected includes patient identity, anamnesis, physical and supporting examinations, diagnosis, therapeutic interventions, and clinical outcomes during treatment and follow-up. The data were then analyzed qualitatively and presented narratively according to the clinical case report format. A 51-year-old woman who developed an acutely painful eye with loss of visual acuity a day before admission. She reported a sensation of pressure and blurry vision in her right eye with no apparent exacerbating factors. The first examination was performed on Uncorrected Visual Acuity (UCVA), where the UCVA was measured as 1/60 OD and 0.4 OS. Slit-lamp examination of the right eye showed moderate conjunctival injection, corneal edema, and pigment deposits on the corneal endothelium. The anterior chamber of both eyes was shallow; gonioscopy findings in the right eye were Schwalbe lines in four quadrants and three in the left. The crystalline lens was clear, and the IOP was measured as 67 mmHg OD and 16 mmHg OS. Acute Primary Angle Closure is an emergency condition that challenges the eye doctor to reduce IOP as soon as possible. The failure of maximum medication to reach the IOP below could lead to the condition to surgery. Even Trabeculectomy has several cautions to consider in this case, but it succeeds in lowering IOP and increasing the patient's visual acuity. Close monitoring is required to avoid the risk of postoperative complications.